2017
DOI: 10.14366/usg.16040
|View full text |Cite
|
Sign up to set email alerts
|

Current status of high-intensity focused ultrasound for the management of uterine adenomyosis

Abstract: While high-intensity focused ultrasound has been used for some time in the management of uterine fibroids, its effectiveness and safety in managing adenomyosis is less well established. A literature review was performed of all eligible reports using this modality as a treatment for adenomyosis. Relevant publications were obtained from the PubMed electronic database from inception through March 2016. Eleven articles, including information from 1,150 treatments and follow-up data from 990 patients, were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 24 publications
1
33
1
3
Order By: Relevance
“…Clinical effects of HIFU for dysmenorrhea in patients with adenomyosis have been investigated and HIFU appears to be effective and safe in the management of symptomatic adenomyosis, which can be considered as an alternative uterine-sparing option for women with this disease (13,14). In addition, Metformin is beneficial for the treatment of adenomyosis (10).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical effects of HIFU for dysmenorrhea in patients with adenomyosis have been investigated and HIFU appears to be effective and safe in the management of symptomatic adenomyosis, which can be considered as an alternative uterine-sparing option for women with this disease (13,14). In addition, Metformin is beneficial for the treatment of adenomyosis (10).…”
Section: Discussionmentioning
confidence: 99%
“…23 In nonrandomized studies, uterine artery embolization (UAE) and MRI-guided focused ultrasound (MgFUS) seem to be promising treatments for adenomyosis, although they were approved by the Food and Drug Administration primarily for leiomyoma therapy. 24,25 Taran et al 24 reported improved symptoms in 50% to 90% of women in several small studies undergoing UAE followed for 1 or more years. Use of MgFUS resulted in a 25% to 66% reduction in bleeding over 12 months in women with adenomyosis.…”
Section: Polypsmentioning
confidence: 99%
“…Use of MgFUS resulted in a 25% to 66% reduction in bleeding over 12 months in women with adenomyosis. 25 Hysterectomy remains definitive therapy for women failing medical treatments.…”
Section: Polypsmentioning
confidence: 99%
“…To date, this HIFU ablation technique has been adopted to treat diverse tumors such as pancreas, brain, prostate, bone, liver, breast, kidney, and uterine tumors. [88][89][90][91][92][93] Among them, pancreatic cancer has been considered an inoperable and unresectable disease at the time of diagnosis. [94] Since the therapy may induce damage of nerve fibers stimulating it, some studies suggest that HIFU can play an important role for treating it without any significant negative effects.…”
Section: Applications Of High-intensity Focused Ultrasoundmentioning
confidence: 99%